2010
DOI: 10.1002/ange.200906949
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Peptide Effects that Control the Activity of Nanoparticles

Abstract: Leichte Änderungen in der Peptidsequenz erhöhten bei gleichbleibender Stabilität die Aktivität von Palladiumnanokatalysatoren auf Peptidbasis. Ein Austausch von Histidin gegen Alanin steigerte die Umsatzfrequenz von 2234 auf 5224, was für eine modulierende Wirkung des Peptids in den Nanomaterialien spricht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 20 publications
1
67
0
Order By: Relevance
“…All of them have demonstrated high affinity for Pd, especially His [35]. Similar to the observations here, His, Asn, and Arg residues of synthetic peptides effectively served as nucleation and stabilizing agents to obtain Pd nanoparticles [36]. Several reports have shown the need for site-directed mutations to insert Cys residues in TMV, providing active sites for the adsorption and reduction of Pd(II) ions and other metal precursors [9,15].…”
Section: Molecular Binding Simulation Vp6-pd(ii)supporting
confidence: 79%
See 1 more Smart Citation
“…All of them have demonstrated high affinity for Pd, especially His [35]. Similar to the observations here, His, Asn, and Arg residues of synthetic peptides effectively served as nucleation and stabilizing agents to obtain Pd nanoparticles [36]. Several reports have shown the need for site-directed mutations to insert Cys residues in TMV, providing active sites for the adsorption and reduction of Pd(II) ions and other metal precursors [9,15].…”
Section: Molecular Binding Simulation Vp6-pd(ii)supporting
confidence: 79%
“…Our results of molecular docking also demonstrated that the high affinity residues on VP6 helped to constrain the size and distribution of Pd particles all over the bio-template external surface. In particular, it has been demonstrated that the presence of His residues is critical within model synthetic peptides, to bio-direct the formation of~2 nm Pd nanoparticles, while their substitution by Ala produce particles with a higher diameter (~4 nm) [36].…”
Section: Molecular Binding Simulation Vp6-pd(ii)mentioning
confidence: 99%
“…[16] We envision that the hollow spherical CoPt nanoparticle superstructures reported herein could potentially be used as magnetically separable reaction vessels for heterogeneous catalysis. [9a, 15, 17] When placed in a magnetic field, the superstructures can be drawn to the wall of a reaction flask ( Figure S10).…”
mentioning
confidence: 99%
“…This result is strong support for the coordination of the oligoprolines to the AgNPs through the carboxylic acid moieties. [16] Further studies to gain a deeper understanding of the mechanisms by which the oligoprolines control the size of the AgNPs are ongoing. [17] In conclusion, we have shown that the size of AgNPs can be controlled by the length of functionalized, rigid, oligoproline-based additives.…”
mentioning
confidence: 99%